Mechanisms of Stigmatization in Family-Based Prevention and Treatment of Childhood Overweight and Obesity - Didde Hoeeg; Katherine L. Frohlich; Ulla Christensen; Dan Grabowski (Children, 2023)
It is well established that overweight and obesity are often accompanied by stigmatization. However, the influence of stigmatization on interventions for overweight and obesity remains unknown. Stigma may be particularly harmful to children. This study aimed to examine how stigmatization affects efforts to reduce childhood overweight and obesity through family interventions. This research was conducted in a socially disadvantaged area in Denmark. Twenty-seven families and forty professionals participated in in-depth interviews or workshops. The data were analyzed using CMO configurations from a realist evaluation and the theory of stigmatization developed by Link and Phelan. Thus, an abductive approach was employed in the analysis, with its foundation rooted in the empirical data. The study found that the mechanisms of stigmatization could 1. restrain professionals and parents from approaching the problem—thereby challenging family recruitment; 2. prevent parents from working with their children to avoid eating unhealthy food for fear of labeling the child as overweight or obese; and 3. cause children with obesity to experience a separation from other slimmer family members, leading at times to status loss, discrimination, and self-stigmatization. The study showed how the mechanisms of stigmatization may obstruct prevention and treatment of childhood obesity through family interventions. It is suggested that the concept of stigma should be incorporated into the program theories of interventions meant to reduce childhood overweight and obesity.